2010
DOI: 10.2217/fmb.09.128
|View full text |Cite
|
Sign up to set email alerts
|

Human Immune Responses in Cryptosporidiosis

Abstract: Immune responses play a critical role in protection from, and resolution of, cryptosporidiosis. However, the nature of these responses, particularly in humans, is not completely understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 100 publications
2
94
0
Order By: Relevance
“…3,4 The immune system of the host is critical in mediating protection from and resolution of cryptosporidiosis. 6 In immunocompetent hosts, the infection is generally asymptomatic or self-limited. However, in immunocompromised hosts including patients with HIV/AIDS, the disease can be chronic, severe, and possibly fatal.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The immune system of the host is critical in mediating protection from and resolution of cryptosporidiosis. 6 In immunocompetent hosts, the infection is generally asymptomatic or self-limited. However, in immunocompromised hosts including patients with HIV/AIDS, the disease can be chronic, severe, and possibly fatal.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical signs of the calves challenged with C. parvum oocysts were similar to symptoms described in previous studies. 2,8 Most of the signs and symptoms correlated with the excretion of oocysts, with the exception of the profile of cytokines. Studies of human and animal cryptosporidiosis have indicated that the cytokine IFN-g is important for resistance to and clearance of the infection.…”
mentioning
confidence: 98%
“…The experiments showed the total protein concentration (antibody) of BALB/c mice has significantly increased after 16th day of oocyst treatment ( (Borad and Ward 2010). Attachment to the apical cell surface by Cryptosporidium, as well as molecules inserted into host cells after attachment, can activate host cell signal pathways and thereby alter cell function.…”
Section: Resultsmentioning
confidence: 99%